The decommissioning of oil and gas fields: Egyptian law and policy. (3rd May 2019) - Elshazly, Mostafa
Abstract: Legal issues around the decommissioning of oil and gas fields have generally been given insufficient attention by energy lawyers in most jurisdictions worldwide. Oil and gas lawyers, and other stakeholders in Egypt, face the same challenge. This article discusses the topic of the decommissioning of oil and gas fields in the context of the legal aspects and the regulatory framework for decommissioning in Egypt, demonstrating the main challenges relating to the legal framework for decommissioning arrangements in the country. At the heart of the legal challenges associated with the decommissioning of oil and gas fields in Egypt lies the most important question: who should pay the associated costs, and when? This article also presents some recommendations to enhance the current regulatory framework for the decommissioning of oil and gas fields in Egypt, to maintain the balance of interests between international oil companies and national oil companies active in Egypt.